Relationship between obesity, adipocykines and osteoarthritis: Review - Quenan, Yoccner Edilson; Osorio, José Henry (Universidad y Salud, 2017)
Introduction: Some adipocytokines expressed by osteoblasts, chondrocytes and synoviocytes are responsible of the inflammation and degradation of the extracellular matrix in the joints, which generates osteoarthritis. Objective: To review the current state of knowledge around the relationship between obesity, adipocytokines and osteoarthritis. Materials and methods: An electronic search was carried out in the databases of BBCS-LILACS, PubMed, IB-PsycINFO, IB-SSCI, IB-SciELO, Scopus and Science Direct in English and Spanish, without limiting the search by date. Clinical trials, meta-analyses, reviews, case reports and classic articles related to obesity and its implications were included as well as osteoarthritis, adipocytokines, adipose tissue and joint inflammation. Results: 822 articles were found; however, 78 documents met the selection criteria for the relevance of the information. This work was divided into three sections: Osteoarthritis and obesity, osteoarthritis and inflammation and osteoarthritis and adipocytokines. Conclusion: Nowadays, obesity is associated with the development of osteoarthritis, as it triggers a series of inflammatory processes mediated by the adipocytokines. Several studies recommend the development of clinical research to understand the behavior of adipocytokines before and during the development of osteoarthritis.